Synthesis, structures, and characterizations of four uranyl coordination polymers constructed by mixed-ligand strategy - Chen, Si-han; Wang, Han-qing (Journal of radioanalytical and nuclear chemistry, 2023)
Uranyl coordination polymers have caught more and more attention due to their rich topological structures and potential practical applications in nuclear waste processing and management. In this work, four novel uranyl coordination polymers have been successfully synthesized by the utilization of a semirigid ligand and uranyl nitrate under hydrothermal reactions through the introducing of different kinds of auxiliary ligands (NaCl, oxalate acid, succinic acid). Therein, the powder X-ray diffraction, Infrared spectroscopy and luminescence properties of compounds 3 and 4 are investigated.